Pendampingan Pelaksanaan English Camp untuk Meningkatkan Kepercayaan Diri Siswa SMP di Makassar dalam Berkomunikasi Bahasa Inggris - A. Kamariah; Citra Dwi Safitri; Muhammad Fahri Jaya Sudding; Musdalifah; Surya Anantatama Sembiring (PT Cendekia Education Center, 2026)
This community service activity aimed to enhance junior high school students’ confidence in communicating in English through an English Camp program conducted at SMP Negeri 46 Makassar. The program employed a participatory approach grounded in experiential learning, encouraging active student involvement in meaningful and contextual communication practices. A series of interactive activities, including ice-breaking sessions, vocabulary building, role plays, group discussions, and speaking performances, were designed to create a supportive and low-anxiety learning environment. The results demonstrated that the English Camp significantly improved students’ confidence in speaking English, as reflected in their increased willingness to participate, greater activeness during activities, and improved courage in expressing ideas. Additionally, observations indicated heightened student engagement, enthusiasm, and interaction throughout the program. These findings suggest that experiential and communicative learning approaches are effective in fostering students’ confidence and participation in language learning. Therefore, the English Camp can be considered an effective alternative strategy to support the development of students’ English communication skills, particularly in building confidence, and it is recommended that similar programs be implemented sustainably and integrated into regular school learning activities to maximize their impact.